A Case of an Infant Diagnosed with Cow's Milk Allergy and Concurrent Meat Allergy via ImmunoCAP ISAC® - So Yoon Jo; Chan Ho Lee; Sung Won Kim; Yoon Ha Hwang (Kosin Medical Journal, 2019)
Approximately 13–20% of infants with milk allergies concurrently exhibit beef allergies. Here, we report a 24-month-old infant who exhibited both pork and beef allergies, concurrently with a milk allergy. The infant's laboratory test results were: 3.73 ISU-E (ISAC standardized unit for IgE) for cow milk β-lactoglobulin, 23.8 ISU-E for casein, 12.8 ISU-E for cow milk Bos d 6 of serum albumin, and 4.85 ISU-E for cat Fel d 2. This case report summarizes an infant patient diagnosed with a meat allergy that was associated with cow's milk allergy, using ImmunoCAP ISAC®. Not only ImmunoCAP ISAC® but also immunocap can be used to diagnose milk allergy and meat allergy at the same time, immunocap testing for component antigen is rare. ImmunoCAP ISAC® is used to diagnose these allergies in our case study, as it has advantage that only 1ml of blood is needed to run various component antigen tests.